Making cheese in Burundi - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
It is technically possible and even profitable to make good cheese without resorting to industrial processes, even in tropical areas. That has been shown by a small business that has been established in Burundi. It has developed a form of raw,...